THE UTILIZATION OF BATIK PATTERN AND NATURAL DYES AS VALUATION OF THE LOCAL VALUE IN BATIK SOCIETY - Dian Widiawati (Fakultas Seni Rupa dan Desain ITB, 2018)
The global awareness in saving the environment and the appreciation towards the values of local wisdom and particular cultures opens up opportunities for the development of natural materials. Products that are considered eco-friendly for its sustainability draws interest of many consumers, one of which includes naturally dyed textile products. By conducting natural dyes in this following research, it is stated not only to be conducted by its environmental issues but also studies upon its trends and local genius. Dusun gempol, kec. Limbangan, kabupaten kendal, is a village located in the center of java among the slopes of west Gunung (mount )Ungaran. This region has varieties of potentials which are gained through aspects including natural and community resources. Both aspects are known to be active in various activities in preserving their nature and culture. There are diverse issues in improving the qualities of batik in this region. The limitation of knowledge and technology is one of the obstacles in gaining good quality materials and wide range of colors. Furthermore,there is a lack of understanding upon the material characteristics which also lead to a disadvantage. Therefore, product diversification is needed by improving the techniques in designing batik (based on local values) to gain the local's ability in producing interesting ornaments that symbolize their culture. Through this research, it is expected to stand as an asset in developing creative natural products in the hope of improving prosperity upon the region's batik crafters, as well as an alternative in solving environmental issues.